The Relationship Between the Upper-Body Strength Characteristics with Velocity and Power Parameters During the Bench Throw Movement: Is Sport Branch An Inportant Factor ? - Serdar Bayrakdaroğlu; İbrahim Can (Türk Spor ve Egzersiz Dergisi, 2020)
The purpose of this study was to investigate whether the relationship between the upper-body strength characteristic with velocity and power parameters during the bench throw exercise shows a significant difference according to sports branches. In accordance with this purpose; a total of 52 athletes (age: 22,8±3,61 years; height: 183,3±10,8 cm; weight: 80,1±13,4 kg) including 13 volleyball players (age: 20,3±1,25 years; height: 194,7±7,51 cm; weight: 87,8±7,22 kg) and 13 handball players (age: 25,4±3,86 years; height: 187,5±8,33 cm; weight: 90,9±14,8 kg) competed in Turkey 1. League together with 13 national martial players (age: 25,0±3,24 years; height: 175,1±6,91 cm; weight: 70,0±7,70 kg) and 13 arm wrestling players (age: 20,6±1,93 years; height: 175,7±5,39 cm; weight: 71,9±7,92 kg) participated as voluntarily. To determine the velocity and power parameters, a bench throw (BT) movement was performed using an external load of 30 % of the participants' body weight and mean propulsive velocity (MPV), peak velocity (PV), mean propulsive power (MPP) and peak power (PP) by the help of an isoinertial velocity transducer (T-Force dynamic measurement system). Shapiro-Wilk normality test, descriptive statistics and Spearman correlation analysis methods were used to evaluate the data. According to the results of the analysis, it was found that there was a statistically significant relationship between the upper-body strenght characteristics with together velocity and power parameters during the BT movement and this relationship shows a statistically significant difference compared to the sports branches. While both the volleyball players and the handball players have a high and positive relationship between the upper-body strength characteristics with together velocity and power values during the BT movement (p lt;0.05); it was found that martial players have only a significant relationship with PV and MPP values. On the other hand, it was determined that arm wrestling players don’t have any statistically significant relationship between both strength and velocity values and characteristic of upper-body strength (p gt;0.05). As a results, it can be asserted that sports branch is an important factor for the relationship between the upper-body strength characteristics with together velocity and power parameters during the bench throw movement.